The Critic Jose Verissimo: Perspectives of the Interpretation - Pereira, Marcio Roberto [UNESP] (Univ Fed Minas Gerais, Fac Letras, 2019)
Published in 1916 and written in most of the literary life of Jose Verissimo, the History of Brazilian Literature: from Bento Teixeira (1602) to Machado de Assis (1908) gathers the several activities of the critic from Para as an active intellectual. With the objective of making a reflection on the facets of the critic and literary historian, this essay analyzes his work of interpretation of the Brazilian nation, through the approximation between the various discourses that make up History. especially literature and education. In proposing the definition of these perspectives, it is noted that the final work of Jose Verissimo has an organicity and a refinement of his analysis criteria.
Keywords: Jose Verissimo; History of Brazilian Literature; literary criticism; education